The Role of Exosomal Epigenetic Modifiers in Cell Communication and Fertility of Dairy Cows - Abeysinghe, Pevindu (Int J Mol Sci, 2020)
Abnormal uterine function affects conception rate and embryo development, thereby leading to poor fertility and reproduction failure. Exosomes are a nanosized subclass of extracellular vesicles (EV) that have important functions as intercellular communicators. They contain and carry transferable bioactive substances including micro RNA (miRNA) for target cells. Elements of the cargo can provide epigenetic modifications of the recipient cells and may have crucial roles in mechanisms of reproduction. The dairy industry accounts for a substantial portion of the economy of many agricultural countries. Exosomes can enhance the expression of inflammatory mediators in the endometrium, which contribute to various inflammatory diseases in transition dairy cows. This results in reduced fertility which leads to reduced milk production and increased cow maintenance costs. Thus, gaining a clear knowledge of exosomal epigenetic modifiers is critical to improving the breeding success and profitability of dairy farms. This review provides a brief overview of how exosomal miRNA contributes to inflammatory diseases and hence to poor fertility, particularly in dairy cows.